(untitled) (Research, Society and Development, 2021)
The knowledge of the dynamics of animal growth over time can be done through non-linear equations. Thus, the objective was to describe and compare the growth of three free-range chicken lineages based on the Gompertz equation. 180 unsexed chickens assigned to three treatments (Pesadão Vermelho, Pescoço Pelado and Carijó Pesado lineages) in a randomized design with six replicates, with 10 birds per experimental unit. Broilers were weighed weekly (until 77 days of age), these data were used to estimate the growth curve and determine the equation parameters (A, B and C) of model used. The comparison tests between the model parameters for each lineage, demonstrated that it is necessary an equation with different A, B and C parameters for each lineages, the lack-of-fit test was not significant (p>0.05), therefore, the equations of the model are suitable to describe the growth of the lineages. The Pesadão Vermelho lineages is heaviest at inflection point and earlier (BWe =1,528 g at 39 days of age), compared to the Pescoço Pelado (BWe=1,185 g at 38 days of age) and the Carijó Pesado (BWe=1,183 g at 51 days of age) lineage. The adjusted Gompertz curves accurately estimated growth curves of the evaluated line-ages. An equation with different A, B and C parameters is required for each lineage. The Pesadão Vermelho lineage is heaviest at maturity. The Carijó Pesado lineage has a slow growth, with low weight at maturity and the oldest age at maturity.